Exploring the value of mental health nurses working in primary care in England: A qualitative study. Issue 6 (August 2017) - McLeod, K.; Simpson, A.
Accessible Summary: What is known on the subject?: Primary care and, in particular, general practice (GP) are often first point of access to health care. International evidence suggests that healthcare systems oriented towards primary care may produce better outcomes, at lower costs and with higher user satisfaction. Despite this, there are noted deficiencies and variations in the quality of care in primary care for patients with mental health problems. What this paper adds to existing knowledge?: Emerging models of providing mental health services in primary care are poorly understood. This paper evaluates a mental health nurse‐led Primary Care Liaison Service (PCLS), developed in 2011 in inner London. The findings suggest that this type of service can improve the quality of care for people presenting with mental health problems within primary care, specifically due to improved integration, clinical effectiveness, patient‐centred care, access and efficiency. The study also highlighted challenges such as staff retention within this new role and setting appropriate referral criteria. What are the implications for practice?: This is a relatively new service, and the cost‐effectiveness is not yet fully understood; however, commissioners may want to consider the potential benefits of a similar service in their area. The extent to which the findings are transferable will depend on service configuration and local demographics which can vary. Further research within this area could give more detail on the impact of such teams on health outcomes, recovery rates, secondary care referrals and accident and emergency attendances, and its cost‐effectiveness. Abstract: Aims/Question: General practice is typically the first point of access to healthcare. This study explores what value a Primary Care Liaison Nurse (PCLN) service, established in 2011, can bring to people with mental health problems in primary care. Method: Semi‐structured interviews were used to elicit participants' experiences and perspectives on the value of a PCLN service. Participants included ten interviews with seven general practitioners and three senior practitioners working in primary care mental health services. Thematic analysis, based on a 6‐phase approach, was used to describe and explore the data collected. Results: Five main themes were derived from the thematic analysis of the interviews relating to: integration; clinical effectiveness; patient centred care; access; and efficiency. Discussion: The study suggests that the PCLN service can improve the quality of care and is generally highly valued by its stakeholders. The study identifies particularly valued elements of the service, including having a duty worker, as well as aspects which could be improved, such as patient criteria. Implications for practice: This is a relatively new service and the cost‐effectiveness is not yet fully understood; however, commissioners may want to consider the potential benefits of a similar service in their area.